2021
DOI: 10.1039/d1ra01593a
|View full text |Cite
|
Sign up to set email alerts
|

Effective reduction of nitrophenols and colorimetric detection of Pb(ii) ions by Siraitia grosvenorii fruit extract capped gold nanoparticles

Abstract: Siraitia grosvenorii fruit extract capped AuNPs exhibited excellent catalytic activity in the reduction of nitrophenols and high sensitivity and selectivity for detection of Pb(ii) ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…4), which was caused by the formation of complexes between Pb 2+ and biomolecules adsorbed on the AuNPs surface. 8 The obtained result confirmed that the agglomeration was the dominant mechanism of the proposed colorimetric probe.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…4), which was caused by the formation of complexes between Pb 2+ and biomolecules adsorbed on the AuNPs surface. 8 The obtained result confirmed that the agglomeration was the dominant mechanism of the proposed colorimetric probe.…”
Section: Resultssupporting
confidence: 67%
“…The negative charge of MT-AuNPs surface is due to the presence of negatively charged oxygen-containing groups such as OH − , COO −. 8 Indeed, the actual results obtained show that the zeta potential of MT-AuNPs at pH of 5.5 was −39.4 mV (Fig. 2c), which was noteworthy higher than that of AuNPs prepared using Sargassum carpophyllum (−0.047 mV) and Crinum latifolium leaf extract (−20.8 mV), suggesting excellent long-term stability of MT-AuNPs solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, AgNPs have also been extensively used for the colorimetric determination of toxic metals in the aquatic environment and biological system due to their strong surface plasmon resonance (SPR), size-and shape-dependent optical properties, and environmental friendliness (Uzunoglu et al, 2020). The principle of colorimetric detection is mainly based on the change in color and/or shift of the SPR peak caused by binding of the target analyte to the metal nanoparticles surface (Le et al, 2021c). These signals can be rapidly detected by UV-Vis spectroscopy and monitored with the naked-eye inspection.…”
Section: Introductionmentioning
confidence: 99%